PENGARUH MOTIVASI TERHADAP SEMANGAT KERJA PEGAWAI BAGIAN UMUM DAN KEPEGAWAIAN PADA KANTOR KECAMATAN MUARADUA OGAN KOMERING ULU SELATAN - Hartono, Rudi (Jurnal Trisna Riset, 2023)
Muaradua Ogan Komering Ulu Selatan District Office In general there is agreement on the need for effective motivation. Therefore, the Muaradua Ogan Komering Ulu Selatan District Office always pays attention to customer service. At the Muaradua Ogan Komering Ulu Selatan District Office, it turns out that motivation has not been implemented properly so that employee morale is not optimal. The problem faced is how motivation influences employee morale at the Muaradua Ogan Komering Ulu Selatan District Office. The purpose of this research is to determine the effect of motivation on employee morale at the Muaradua Ogan Komering Ulu Selatan District Office and to be useful as reference material for further research regarding employee motivation and morale. The hypothesis proposed is that motivation has a positive effect on employee morale at the Muaradua Ogan Komering Ulu Selatan District Office. Data collection and processing using library studies and field studies using observation, questionnaires, interviews and documentation. From the results of the article, the correlation between motivation in efforts to increase employee morale at the Muaradua Ogan Komering Ulu Selatan District Office obtained an r figure of 0.57. After consulting with conservation standards, it is between 0.400- 0.599 which is included in the moderate correlation. So it can be said that there is a moderate influence between motivation on employee morale at the Muaradua Ogan Komering Ulu Selatan District Office.